Electronic Learning and Open Educational Resources in the Health Sciences in Ghana - Adanu, RMK (Ghana Medical Association, 2010)
OBJECTIVES: To determine whether a group of Ghanaian students are able to easily use electronic learning material and whether they perceive this method of learning as acceptable. SETTING: The University of Ghana Medical School (UGMS) and the School of Medical Sciences (SMS), Kwame Nkrumah University of Science and Technology (KNUST) PARTICIPANTS: One hundred and fifty third year medical students at SMS and nineteen fifth year medical students at UGMS METHODS: Two e-learning materials were developed, one on the polymerase chain reaction and the other on total abdominal hysterectomy and these were distributed to selected medical students. Two weeks after the distribution of the programmes, a one-page, self-administered questionnaire was distributed to the target groups of students at the two institutions. RESULTS: Ninety three percent (139) of respondents at KNUST and 95% (18) at UG report having access to a computer for learning purposes. All of the UG students viewed the TAH programme; 82% (130) of the KNUST students viewed the PCR animations. All students who viewed the programmes at both institutions indicated that the e-learning pro-grammes were “more effective” in comparison to other methods of learning. CONCLUSION: Computer ownership or availability at both medical schools is sufficient to permit the distribution and viewing of e-learning materials by students and the medical students considered both programmes to be very helpful.